Widespread contamination of coastal sediments in the Transmanche Channel with anti-androgenic compounds. Issue 2 (30th June 2015) - Alvarez-Muñoz, Diana; Indiveri, Paolo; Rostkowski, Pawel; Horwood, Julia; Greer, Emily; Minier, Christophe; Pope, Nick; Langston, William J.; Hill, Elizabeth M.
Highlights: Anti-androgen (AA) activity was detected in extracts of coastal sediments. AA activity was 0.2–224.3 ± 38.4 μg flutamide equivalents/g dry weight of sediment. AA activity was present in clams due to uptake of a series of 4 or 5 ring PAHs. Abstract: This study analysed the levels of androgen receptor antagonist activity in extracts of coastal sediments sampled from estuaries in southern UK and northern France. Anti-androgenic (AA) activity varied between <0.2 and 224.3 ± 38.4 μg flutamide equivalents/g dry weight of sediment and was significantly correlated with the total organic carbon and silt content of samples. AA activity was detected in tissues extracts of clams, Scrobicularia plana, sampled from a contaminated estuary, some of which was due to uptake of a series of 4 or 5 ring polycyclic aromatic hydrocarbons (PAHs). Initial studies also indicated that fractionated extracts of male, but not female, clams also contained androgen receptor agonist activity due to the presence of dihydrotestosterone in tissues. This study reveals widespread contamination of coastal sediments of the Transmanche region with anti-androgenic compounds and these contaminants should be investigated for their potential to disrupt sexual differentiation in aquatic organisms.